Phosphorylation of Syntaxin‐1a by casein kinase 2α regulates pre‐synaptic vesicle exocytosis from the reserve pool. Issue 5 (6th September 2020) - Shi, Vanilla (Hua); Craig, Tim J.; Bishop, Paul; Nakamura, Yasuko; Rocca, Dan; Wilkinson, Kevin A.; Henley, Jeremy M.
Abstract: The t‐soluble NSF‐attachment protein receptor protein Syntaxin‐1a (Stx‐1a) is abundantly expressed at pre‐synaptic terminals where it plays a critical role in the exocytosis of neurotransmitter‐containing synaptic vesicles. Stx‐1a is phosphorylated by Casein kinase 2α (CK2α) at Ser14, which has been proposed to regulate the interaction of Stx‐1a and Munc‐18 to control of synaptic vesicle priming. However, the role of CK2α in synaptic vesicle dynamics remains unclear. Here, we show that CK2α over‐expression reduces evoked synaptic vesicle release. Furthermore, shRNA‐mediated knockdown of CK2α in primary hippocampal neurons strongly enhanced vesicle exocytosis from the reserve pool, with no effect on the readily releasable pool of primed vesicles. In neurons in which endogenous Stx‐1a was knocked down and replaced with a CK2α phosphorylation‐deficient mutant, Stx‐1a(D17A), vesicle exocytosis was also increased. These results reveal a previously unsuspected role of CK2α phosphorylation in specifically regulating the reserve synaptic vesicle pool, without changing the kinetics of release from the readily releasable pool. Abstract : Syntaxin‐1a (Stx‐1a) is an essential component of the pre‐synaptic release machinery. Stx‐1a is phosphorylated by the kinase CK2α, however, the consequent impact on pre‐synaptic exocytosis is poorly understood. We show that reducing Stx‐1a phosphorylation by knockdown of CK2α enhances pre‐synaptic vesicle exocytosis from the reserve pool, whereas over‐expressing CK2α reduces exocytosis. Replacement of endogenous Stx‐1a with a mutant that cannot be phosphorylated by CK2α enhances exocytosis from the reserve pool. Together, our results support a model whereby phosphorylation of Stx‐1a by CK2α acts to specifically restrict the size of the reserve pool of vesicles, resulting in reduced vesicle exocytosis.